(untitled) (The Agriculturists, 2014)
Seed is the foundation of agriculture for enhancing crop production. The economic benefits from the improved quality seed production help scaling up the livelihood standard as well as nutritional status of the common people. The study was carried out in three districts namely Jamalpur, Gazipur and Manikganj to identify the socio-economic dimensions of the government seed production project beneficiaries persuading profitability of rice seed production. Data were collected through intensive survey of randomly selected 211 sample respondents using pre-tested interview schedule. To examine the profitability of rice seed production, the gross margin and cost benefit analysis were carried out. Co-efficient of correlation and multiple stepwise regressions were employed to find out the determinants of profitability in rice seed production. Rice seed production was not found to be so profitable as investment in rice seed cultivation can produce average BCR of only up to 1.44, where highest BCR was found in Jamalpur (1.58) compared to Manikganj (1.48) and Gazipur (1.26). The results revealed that socio-economic factors have a profound influence on profitability of rice seed production as these factors combined explained 54.9 percent variation. Farm size, contact with information sources, knowledge on quality rice production and age of the respondents were identified as significant contributors in profitability of rice seed production, whereas contact with information sources was the single most influential factor (24.6%). Therefore, steps may be taken so that the seed-growers could directly be linked with more information sources dealing with seed production and marketing through the government initiatives to boost up the production as well as to ensure appropriate price of the farmers home grown seed. DOI: http://dx.doi.org/10.3329/agric.v12i1.19578 The Agriculturists 2014; 12(1) 33-40